Respuesta :
Answer:
-1
Step-by-step explanation:
by collecting like terms
-17h -4h -2h = 19+4
-23h = 23( divide both sides by coed. of h)
h= -1
First you simplify the equation by adding or subtracting like-numbers. Simplify all of the numbers with h.
1) -23h -4 = 19
Then, add four to both sides to get the variables on one side to their self.
2) -23h = 23
Lastly, Divide both sides by -23 to get h by itself.
h = -1
1) -23h -4 = 19
Then, add four to both sides to get the variables on one side to their self.
2) -23h = 23
Lastly, Divide both sides by -23 to get h by itself.
h = -1